-21-7p=-4(2p+7)

Simple and best practice solution for -21-7p=-4(2p+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -21-7p=-4(2p+7) equation:



-21-7p=-4(2p+7)
We move all terms to the left:
-21-7p-(-4(2p+7))=0
We calculate terms in parentheses: -(-4(2p+7)), so:
-4(2p+7)
We multiply parentheses
-8p-28
Back to the equation:
-(-8p-28)
We get rid of parentheses
-7p+8p+28-21=0
We add all the numbers together, and all the variables
p+7=0
We move all terms containing p to the left, all other terms to the right
p=-7

See similar equations:

| -3(1+7x)-3(-6x+6)=x-5+8 | | x(x-4)(x^2+4x+16)=0 | | -7(y-6)=3y+22 | | -12=-6(3+y) | | 90+6x=-7.5+30 | | -2x−5=−4x+2 | | 8y+4=3(y-7) | | 42x+17=29x+199 | | 6s-4=8(2+2s) | | C=38.98+0.50x | | 2x−5=−4x+2 | | 27-11x=X | | -5(y-5)=-7y+9 | | 8-3z=26 | | 4x^2-54x+144=0 | | 140x-80=20(7x-4) | | 18=-3w+7(w+2) | | (9/x-2)=(18/x) | | 3r-2=-9+2r | | -4x+4x-5=17 | | 0=45-(1.7*d) | | 12-9x=3x(x+10) | | -36=-7y+2(y-8) | | 6x+30x-5=9(4x+6) | | -3y+8+3y=8 | | 4v+7(v+5)=2 | | 3y=15y-72 | | 1-10n=-169 | | 3-6b=20 | | 2^-x=410 | | 6(n+6)=3(n+7) | | (5w+24)+(2w+13)=16 |

Equations solver categories